Development of texture and seismic anisotropy during the onset of subduction. (31st January 2014) - Di, J. F.; Walker, A. M.; Li, Z.‐H.; Wookey, J.; Ribe, N. M.; Kendall, J.‐M.; Tommasi, A.
<x xml:space="preserve">Abstract</x> [1] How reliable are shear wave splitting measurements as a means of determining mantle flow direction? This remains a topic of debate, especially in the context of subduction. The answer hinges on whether our current understanding of mineral physics provides enough to accurately translate between seismic observations and mantle deformation. Here, we present an integrated model to simulate strain‐history‐dependent texture development and estimate resulting shear wave splitting in subduction environments. We do this for a mantle flow model that, in its geometry, approximates the double‐sided Molucca Sea subduction system in Eastern Indonesia. We test a single‐sided and a double‐sided subduction case. Results are compared to recent splitting measurements of this region by Di Leo et al. (2012a). The setting lends itself as a case study, because it is fairly young and, therefore, early textures from the slab's descent from the near surface to the bottom of the mantle transition zone—which we simulate in our models—have not yet been overprinted by subsequent continuous steady state flow. Second, it allows us to test the significance of the double‐sided geometry, i.e., the need for a rear barrier to achieve trench‐parallel subslab mantle flow. We demonstrate that although a barrier amplifies trench‐parallel subslab anisotropy due to mantle flow, it is not necessary to produce trench‐parallel fast directions per se. In a simple model of A‐type olivine lattice‐preferred orientation and one‐sided subduction, trench‐parallel fast directions are produced by a combination of simple shear and extension through compression and pure shear in the subslab mantle.